2012
DOI: 10.1016/j.molstruc.2012.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Valence XPS, IR, and C13 NMR spectral analysis of 6 polymers by quantum chemical calculations

Abstract: Valence XPS (VXPS), IR, and C13 NMR spectra of 6 polymers (PE, PS, PMMA, PET, Nylon6, PVC) have been analyzed using the model oligomers from B3LYP/6-31+G(d, p) basis calculations in GAUSSIAN 09. We simulated VXPS of the polymers by the negative of the orbital energies of the ground electronic state at the geometry-optimization of the model oligomers. The simulated VXPS spectra by B3LYP/6-31+G(d, p) basis level were compared with simulated spectra by calculations of SAOP method of ADF program. Simulated IR, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The radiation energy of widespread sources (e.g., MgK α : 1253.6 eV, AlK α : 1486.6 eV) allow for structured spectra with a greater number of accessible IEs compared with ultraviolet sources. We note that valence region analyses based on deMon DFT and ADF calculations have become widespread, as reported in representative informative studies …”
Section: Introductionmentioning
confidence: 83%
“…The radiation energy of widespread sources (e.g., MgK α : 1253.6 eV, AlK α : 1486.6 eV) allow for structured spectra with a greater number of accessible IEs compared with ultraviolet sources. We note that valence region analyses based on deMon DFT and ADF calculations have become widespread, as reported in representative informative studies …”
Section: Introductionmentioning
confidence: 83%
“…Chong et al , and Endo et al later showed that the most accurate results are obtained with an occupation of 1/3 and calculations performed as unrestricted. This latter development is known as the unrestricted Generalized Transition State (uGTS) theory.…”
Section: Introductionmentioning
confidence: 98%
“…It reflects that most of the carbon in nanofibers is saturated carbon, and the large amount of saturated carbon also means the nanofibers have a stable physical structure. What should be noticed is that the increasing of the peaks in SnSb/C/DLC precursor nanofibers at 30.5 ppm means sp 3 -hybridized DLC nanoparticles belong to the tetrahedral carbon and exhibit high hardness values [11]. More tetrahedral carbon also indicates that the generated DLC nanoparticles have a better electrochemical stability.…”
Section: Characterizations and Electrochemical Evaluationmentioning
confidence: 97%